2003
DOI: 10.1097/01.rlu.0000093089.53875.3e
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma Detected on Tc-99m-Labeled Red Blood Cell Imaging

Abstract: A 61-year-old-man with persistent anemia was referred for a Tc-99m-labeled red blood cell (RBC) scan to detect any source of gastrointestinal bleeding. RBC scintigraphy revealed a hypervascular mass in the left renal fossa with functional loss in that kidney, suggesting the possibility of a renal cell carcinoma (RCC). Computed tomography confirmed this. Most RCC tumors are hypervascular on conventional angiography, with a maximum incidence in men in the sixth decade. The incidental diagnosis of RCC during radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Nonenteric bleeding activity can move and accumulate and confuse interpretation, including intraperitoneal hemorrhage (108,109), mesenteric bleeding (110), and soft-tissue hematoma/hemorrhage (111)(112)(113)(114)(115)(116). Both benign and malignant neoplasms and metastatic disease can cause hyperemia and bleeding when ulcerated or necrotic (117)(118)(119)(120)(121)(122)(123)(124)(125)(126). Retroperitoneal bleeding can show focal uptake that grows in intensity but is not expected to move in a luminal pattern (127).…”
Section: Increased Rbc Activity Due To Other Causesmentioning
confidence: 99%
“…Nonenteric bleeding activity can move and accumulate and confuse interpretation, including intraperitoneal hemorrhage (108,109), mesenteric bleeding (110), and soft-tissue hematoma/hemorrhage (111)(112)(113)(114)(115)(116). Both benign and malignant neoplasms and metastatic disease can cause hyperemia and bleeding when ulcerated or necrotic (117)(118)(119)(120)(121)(122)(123)(124)(125)(126). Retroperitoneal bleeding can show focal uptake that grows in intensity but is not expected to move in a luminal pattern (127).…”
Section: Increased Rbc Activity Due To Other Causesmentioning
confidence: 99%
“…99m Tc-labeled RBC scintigraphy is a very useful method for detecting active GI bleeding; previous studies have reported the sensitivity and specificity of 99m Tc-labeled RBC scintigraphy as 78.6-97 % and 70.4-100 %, respectively [4,5]. However, other studies have reported potential pitfalls, unanticipated and false-positive results, but most of them could be excluded because of untypical patterns of radioactivity [1,[4][5][6][7][8]. The present study could also rule out the possibility of GI bleeding.…”
mentioning
confidence: 99%
“…These radiopharmaceuticals can be used for important applications, including imaging of cardiovascular system (Niemeyer et al, 1995;Crandall et al, 2008;Javadi et al, 2011), peripheral arterial blood flow (Blond and Madsen, 2000;Harel et al, 2005;Hsieh et al, 2009), evaluation of gastrointestinal bleeding (Zaman et al, 2004;Wong et al, 2004;Olds et al, 2005;Schillaci et al, 2009;Dolezal et al, 2011), measurement of red cell volume (Hladik III et al, 1987), hepatic hemangiomas (Artiko et al, 2004;Verdu et al, 2005;Yarlagadda et al, 2008), renal carcinoma (Cortes et al, 2003), splenic reticuloendothelial system (Jin et al, 2004;Slart et al, 2004) and imaging infection (Stoeckli et al, 1996) Tc to internal structures (Early and Soddee, 1995;Dewanjee et al, 1982). The band-3 anion transport system and calcium channels may be involved in transport of 99m TcO 4 -and Sn…”
Section: Introductionmentioning
confidence: 99%